1982
DOI: 10.1002/bem.2250030303
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency amplitude modulated microwave fields change calcium efflux rates from synaptosomes

Abstract: Calcium (45Ca2+) efflux from preloaded synaptosomes was studied with a continuous perfusion technique and the rate constants of a two-phase efflux process calculated. When 16-Hz sinusoidally amplitude modulated 450-MHz microwave field (maximal incident intensity 0.5 mW/cm2, modulation depth 75%) was applied during the second phase, the rate constant increased by 38%. Unmodulated or 60-Hz modulated signals were not effective. This microwave field-induced change can be distinguished from CaCl2-stimulated 45Ca2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

1982
1982
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 19 publications
3
33
1
Order By: Relevance
“…The mechanisms by which RF radiation interacts with metals or ions in cells and tissues remain unknown. Although it has been reported that RF radiation changed calcium efflux rates in culture cells [7,19], whether RF radiation affected calcium efflux or not was still contradictory [6]. The present results showed that exposure to RF radiation at 40 kHz induced hepatic injury in LEC rats, although adverse effects were not found in normal control rats (WKAH rats) after exposure to RF radiation.…”
Section: Discussioncontrasting
confidence: 60%
“…The mechanisms by which RF radiation interacts with metals or ions in cells and tissues remain unknown. Although it has been reported that RF radiation changed calcium efflux rates in culture cells [7,19], whether RF radiation affected calcium efflux or not was still contradictory [6]. The present results showed that exposure to RF radiation at 40 kHz induced hepatic injury in LEC rats, although adverse effects were not found in normal control rats (WKAH rats) after exposure to RF radiation.…”
Section: Discussioncontrasting
confidence: 60%
“…The (14) and in its synaptosomal fractions (15) and are similarly ineffective in modulating cell-mediated cytotoxicity of T lymphocytes (16), phenomena that are -strongly responsive to radio and microwave fields amplitude modulated at frequencies <100 Hz. We have confirmed that these fields produced an electrical gradient of ==I.O mV/cm around a 1-cm ioop in the spatially homogeneous portion ofthe field between the coils and that the expected peak extracellular current density in homogeneous conducting electrolytes would be =zzl.0 pA/cm2 ('13 (6).…”
Section: Methodsmentioning
confidence: 99%
“…One hypothesis is that a field could induce changes in the cellular membranes, influencing either directly or indirectly receptor-binding properties of the ligands such as Ca 2+, neurotransmitters, hormones, etc. [11,12]. Another possibility is that the magnetic fields could act through cyclotron effects [13].…”
Section: Introductionmentioning
confidence: 99%